Benign Hepatic Neoplasms: An Imaging Review - Behera, Rajendra Kumar; Chandola, Stuti; Goyal, Ankur; Sharma, Raju (Journal of Gastrointestinal and Abdominal Radiology, 2023)
Benign liver neoplasms are commonly encountered in clinical practice. Lesions like typical hemangioma may be confidently diagnosed on ultrasound, but for the majority of other liver lesions, multiphasic computed tomography (CT) and magnetic resonance imaging (MRI) are usually warranted. In lesions like adenomas, making the diagnosis alone is not sufficient; rather subcategorization is important to optimally manage these cases. Additionally, commonly observed variant lesions like the inflammatory subtype of hepatocellular adenoma and focal nodular hyperplasia mimic each other, which exacerbates the diagnostic dilemma. When observing cystic lesions, mucinous cystic neoplasm of the liver (MCN-L) needs to be differentiated from the more common non-neoplastic etiologies like hydatid cysts. Radiologists should also be acquainted with features of rare hepatic neoplasms like angiomyolipoma, paraganglioma, and inflammatory pseudotumor. In this review, we discuss the salient features and differentiating points to suggest the most likely diagnosis.
Keywords: benign liver lesions; hepatocellular adenoma; focal nodular hyperplasia; mucinous cystic neoplasms; liver